Revitalisasi PAI melalui Inovasi Teknologi: Menghadapi Era Digitalisasi - Syauqi Musfirah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2024)
The objective of this research is to identify the updates in Islamic Religious Education (PAI) through the utilization of new technologies in the context of constant digitization. Islamic religious education plays a crucial role in the lives of Muslims. To keep pace with current developments, Islamic religious education is also adapted and redesigned to continuously align with the needs of today's society. Technology plays a significant role in these changes. Questions arising include: How can new technologies be employed in Islamic religious education in the digital era? In the age of digitization, will technological innovations have a positive impact on Islamic religious education? This research involves a literature review that examines articles, journals, and academic literature related to Islamic boarding schools (pesantren) and their development. Secondary data from relevant books and research findings are used as data sources. The data collection method employed is a literature review. The findings of this research indicate that the digital era should be seen as a golden opportunity to maximize the potential of Islamic religious education and educate a generation with strong moral values and character. Thus, Islamic religious education will be able to play its role and strengthen its presence in the midst of global civilization by offering creative solutions in the field of education both in the present and the future.